The Implementation Of Discovery Learning Model To Enhance Studentâs Actualization in Knowledge Discovery - Pigawati, Bitta; Basuki, Yudi (Indonesian Journal of Curriculum and Educational Technology Studies, 2016)
Paradigma pendidikan universal memperlakukan peserta didik sebagai subjek merupakan penghargaan terhadap peserta didik sebagai manusia yang utuh. Peserta didik memiliki hak untuk mengaktualisasikan dirinya secara optimal dalam aspek kecerdasan intelektual, spiritual, sosial, dan kinestetik. Diperlukan penentuan  model pembelajaran yang sesuai  dalam mengimplementasikan metode pembelajaran student centered learning  bagi peserta didik.  Penelitian ini bertujuan mengevaluasi penerapan model discovery learning. Subyek penelitian adalah mahasiswa peserta kuliah geologi lingkungan Departemen Perencanaan Wilayah dan Kota Fakultas Teknik Undip. Hasil penelitian menunjukkan model discovery learning lebih optimal dilakukan pada topik perkuliahan yang sifatnya kompleks dan memerlukan pemahaman yang mendalam.   The general paradigm of education to treat learners as subjects has been regarded as a respect for the learners as a whole human being.Learners have the right to perform optimal self-actualization in the aspects or intellectual, spiritual, social, and kinesthetic quotient. Based on that, a learning model which can be used to implement student centered learning method for learners should be established. The research was aimed to evaluate the implementation of discovery learning model. The subjects were the students enrolled in environmental geology class, Urban and Regional Planning Department, Faculty of Engineering, Diponegoro University. The result shows that discovery learning model is more optimal to be applied in complex lecturing topic which needs deeper understanding.